2021
DOI: 10.1051/e3sconf/202124402022
|View full text |Cite
|
Sign up to set email alerts
|

Technology of caper (capparis spinosa) seed preparation for cultivation and cultural growth

Abstract: This article discusses the importance of capers plant, its biological and, medicinal properties of the plant for human health, its chemical composition and important biological and physiological properties in preparing the seeds for planting for cultural cultivation, differences from other seeds, types of chemical stimulants and their concentrations scientific significance has been shown. There is information on planting times and planting depths, and, schemes and technologies for cultivating capers, and techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Although the fruits contain many seeds, they have a very low germination percentage. Several authors have reported various studies to improve its germination and try to break the possible physical dormancy with different types of scarification, whether mechanical, chemical, thermal, or biological, [12][13][14][15], as well as being able to break the physiological dormancy with the use of gibberellic acid (GA 3 ) and potassium nitrate, as reported by [16][17][18][19]. It has been proven that scarification with sulfuric acid and the addition of GA 3 have improved the germination percentage [12,20], which Plants 2022, 11, 202 2 of 10 has led to the hypothesis that caper seeds can present physical dormancy (due to the impermeability of their cover) and physiological dormancy imposed by the embryo.…”
Section: Introductionmentioning
confidence: 99%
“…Although the fruits contain many seeds, they have a very low germination percentage. Several authors have reported various studies to improve its germination and try to break the possible physical dormancy with different types of scarification, whether mechanical, chemical, thermal, or biological, [12][13][14][15], as well as being able to break the physiological dormancy with the use of gibberellic acid (GA 3 ) and potassium nitrate, as reported by [16][17][18][19]. It has been proven that scarification with sulfuric acid and the addition of GA 3 have improved the germination percentage [12,20], which Plants 2022, 11, 202 2 of 10 has led to the hypothesis that caper seeds can present physical dormancy (due to the impermeability of their cover) and physiological dormancy imposed by the embryo.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have tried to improve caper seed germination and to break the possible physical dormancy with different types of scarifications (mechanical, chemical, thermal or biological) [5][6][7][8] and to break the physiological dormancy with the use of gibberellic acid (GA 3 ) and potassium nitrate [9][10][11][12]. The ultrasound application has been used in seed germination studies of both cultivated plants and weeds [13][14][15][16][17][18], but it is one of the least-studied methodologies in caper seeds.…”
Section: Introductionmentioning
confidence: 99%